Qualidade de água de abastecimento na zona rural de Santa Rita – PB e propostas de melhoria - Silva, Andréa dos Santos (2019)
Rural areas use alternative sources of water to meet domestic demand and provide economic development. The agricultural activities and the lack of rural sanitation imply a risk of contamination by effluents from the activities developed around the springs present in this space. The objective of this work was to evaluate the water quality of the underground water supply sources of the rural area of Santa Rita (PB) and propose ways of improvement. The methodology consisted of the collection and analysis of water and comparison with legislation, analysis of the water supply system, investigation of the land uses in the perimeter of protection of the wells and survey of the perception of the community. The results demonstrated the presence of Coliforms in 80% of the collection points, which characterizes the non-compliance with the microbiological standard required by the legislation. Regarding the physical and chemical parameters, point unconformities were verified. It was also observed that the surroundings of several wells studied are surrounded by sanitary incompatible activities. From the structural point of view, the supply system does not meet the current consumption demand and shows signs of deterioration. Thus, the presented conditions are potential vectors of risk of contamination of the water used. According to the realized perception survey, most of the rural households do not have access to adequate water supply. Despite this, 50% of respondents believe that the water used is not at risk of contamination. Thus, 75% do not use any form of home treatment of the water consumed. Therefore, it is necessary to restructure the entire water supply system, implement preventive operation routines and adopt the disinfection step. For the sanitary improvement of the existing homes, near the catchment points, it is proposed to adopt social technologies of basic sanitation such as the evapotranspiration tank - for the black waters - and banana tree circles - for the gray waters. All this, coupled with environmental education campaigns of the population regarding the risks of contamination of the water used, so that they are encouraged to carry out some type of home water treatment.Thus, this research is expected to serve as a subsidy to ensure that supply more sustainable basis for present and future generations.